Recycling and environmental issues of lithium-ion batteries: Advances, challenges and opportunities - Costa, Carlos Miguel Silva (2021)
Lithium-ion batteries, LIBs are ubiquitous through mobile phones, tablets, laptop computers and many other consumer electronic devices. Their increasing demand, mainly driven by the implementation of the electric vehicles, brings several environmental issues related to the mining, extraction and purification of scarce materials such as cobalt, nickel and lithium. This work provides an overview on the relevance of recycling LIBs and their environmental impact. It also analyses the components of LIBs and evaluates their value in the world market. Although there is a strong focus on lithium, other critical metals, such as cobalt and nickel, are also addressed. Different recycling methods for the different battery components are reported together with the main achievements. The advantages and disadvantages of the different used methods are discussed, and their environmental issues are considered. Finally, the main environmental issues associated with the production, use and end of life of LIBs for electric vehicles are described.